MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI BILANGAN CACAH MELALUI MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE TEAMS GAMES TOURNAMENT (TGT) DI KELAS V UPT SD NEGERI SIDOREJO 2 TUBAN - Dwi Mei Tanti; Lilik Mawartiningsih; Rita Yuliastuti; Fadhilatun Nisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to improve students’ mathematics learning outcomes on the topic of whole numbers through the implementation of the Cooperative Learning model using the Teams Games Tournament (TGT) type among fifth-grade students at UPT SD Negeri Sidorejo 2 Tuban. This study employed a Classroom Action Research (CAR) design conducted in two cycles. Each cycle consisted of four stages: planning, action implementation, observation, and reflection. The subjects of the study were 16 students, consisting of 5 male students and 11 female students. Data were collected through learning achievement tests and observations conducted during the learning process. The data were analyzed descriptively by calculating the students’ average scores and learning mastery percentages. The results showed an improvement in students’ learning outcomes following the implementation of the Cooperative Learning model using the TGT type. In the pre-cycle stage, the students’ average score was 63.13, with a learning mastery percentage of 43.75%, or 7 students. In Cycle I, the average score increased to 72.81, with a learning mastery percentage of 68.75%, or 11 students. In Cycle II, the average score increased further to 81.56, with a learning mastery percentage of 81.25%, or 13 students. These results indicate that the research success criterion, namely a minimum of 80% of students achieving the Learning Objective Achievement Criteria (KKTP), was achieved in Cycle II. Therefore, the implementation of the Cooperative Learning model using the Teams Games Tournament (TGT) type can improve mathematics learning outcomes on the topic of whole numbers among fifth-grade students at UPT SD Negeri Sidorejo 2 Tuban.